2007
DOI: 10.1002/syn.20411
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talking between 5‐HT3 and GABAA receptors in cultured myenteric neurons

Abstract: We recorded whole-cell ion currents induced by gamma-aminobutyric acid (I(GABA)) and serotonin (I(5-HT)) to investigate and characterize putative interactions between GABA(A) and 5-HT(3) receptors in myenteric neurons from the guinea pig small intestine. I(GABA) and I(5-HT) were inhibited by bicuculline and ondansetron, respectively. Currents induced by the simultaneous application of both, GABA and 5-HT (I(GABA+5-HT)) were significantly lower than the sum of I(GABA) and I(5-HT), indicating the existence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Moreover, in one study both the 5-HT 3 antagonist zacopride and the agonist mCPBG produced anxiogenic effects (Andrews and File, 1992). Such inconsistencies were explained by 5-HT 3 effects on serotonin release (Blier and Bouchard, 1993;Bagdy et al, 1998) and interactions with noradrenaline, glycine, and GABA neurotransmission (Mongeau et al, 1994;Maksay, 1996;Chesnoy-Marchais et al, 2000;Miranda-Morales et al, 2007). Our findings suggest that the highly inconsistent effects of 5-HT 3 ligands on anxiety are at least partly explained by the interaction between 5-HT 3 -mediated serotonergic neurotransmission and cannabinoid signaling.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, in one study both the 5-HT 3 antagonist zacopride and the agonist mCPBG produced anxiogenic effects (Andrews and File, 1992). Such inconsistencies were explained by 5-HT 3 effects on serotonin release (Blier and Bouchard, 1993;Bagdy et al, 1998) and interactions with noradrenaline, glycine, and GABA neurotransmission (Mongeau et al, 1994;Maksay, 1996;Chesnoy-Marchais et al, 2000;Miranda-Morales et al, 2007). Our findings suggest that the highly inconsistent effects of 5-HT 3 ligands on anxiety are at least partly explained by the interaction between 5-HT 3 -mediated serotonergic neurotransmission and cannabinoid signaling.…”
Section: Discussionmentioning
confidence: 60%
“…However, a recent study for the first time described a cross-talk between 5-HT 3 Rs and GABA A Rs in myenteric neurons using whole-cell recordings (Miranda-Morales et al, 2007), by providing evidence for current occlusion on simultaneous activation of these two receptors. The cross-talk as observed at saturating concentration of agonists for both receptors occurred immediately after the application of the two agonists, possibly suggesting that the two receptors are located very close to each other.…”
Section: Cross-talk Of Gabaa With Serotonin Receptorsmentioning
confidence: 99%
“…9 A number of studies suggest that alterations in 5-HT signaling may contribute to colonic motor disorders but inconsistencies exist among these investigations. 3,11 Unraveling the exact modes of action of 5-HT in regulating gut motor activity is complicated because of the multiple sources of 5-HT, the multiple receptor subtypes, pre-and postsynaptic actions, 3,12 potentially constitutively active receptors and the many targets of 5-HT. 13,14 This is particularly true for whole organ studies; but such studies remain essential since most motor patterns are not revealed in simpler preparations such as muscle strips.…”
Section: Introductionmentioning
confidence: 99%